Clinical and environmental considerations for neonatal, office-based circumcisions compared with operative circumcisions - Press, Benjamin; Jalfon, Michael; Solomon, Daniel; Hittelman, Adam Benjamin (Frontiers in Urology, 2024)
Neonatal male circumcision is a commonly performed procedure in the United States. Circumcisions are performed at various ages by a variety of clinical providers for multiple reasons, including religious, cultural, personal, and medical indications. In the United States, neonatal circumcision is routinely performed by non-urologic providers in the hospital within the first few days of life or as a religious ceremony on the 8th day of life. If neonatal circumcision is deferred in the hospital and subsequently not performed in the outpatient setting, it is then typically performed in the operating room under general anesthesia after 6 months of life. Neonatal circumcision is supported by both the American Academy of Pediatrics (AAP) and the American College of Obstetricians and Gynecologists (ACOG) due to the belief that the health benefits outweigh the minimal risk of the procedure. Despite this, neonatal circumcision rates have decreased in the United States in recent decades, in part due to access to the procedure, often related to changing insurance coverage. This has led to increased rates of operative circumcisions. Operative circumcisions are more costly to the healthcare system, subject the patient to cardiopulmonary and potentially neurotoxic effects of general anesthesia, and carry an increased environmental footprint, compared to neonatal circumcision. The intention of this paper is not to promote or justify circumcision for all patients, but rather to compare the clinical and environmental impact of neonatal versus operative circumcisions.